The Influence of Organizational Culture and Financial Literacy on Entrepreneurial Intentions in Women's Organizations Through Entrepreneurial Motivation as an Intervening Variable (Case Study: Fatayat NU DKI Jakarta) - Maesaroh, Siti; Widyastuti, Umi; Wolor, Christian Wiradendi (MultiTech Publisher, 2024)
Entrepreneurship is a crucial element in the economy that drives innovation, creates job opportunities, and enhances societal well-being. In the context of women's organizations, particularly in Indonesia, developing entrepreneurial intentions and motivations is strategically important. Fatayat Nahdlatul Ulama (Fatayat NU), as one of the largest women's organizations in Indonesia, plays a significant role in encouraging its members to engage in entrepreneurship. This research aims to analyze the influence of organizational culture and financial literacy on entrepreneurial intentions among female organization members, with entrepreneurial motivation as an intervening variable. The research methodology employed Structural Equation Modeling (SEM) using the AMOS software. Data were collected through questionnaires distributed to 332 Fatayat NU members in DKI Jakarta. The results indicate that organizational culture significantly and positively influences entrepreneurial motivation, and financial literacy also has a positive and significant impact on entrepreneurial motivation. Organizational culture significantly and positively affects entrepreneurial intentions, while financial literacy also significantly and positively influences entrepreneurial intentions. Moreover, entrepreneurial motivation proves to be a significant intervening variable in the relationship between organizational culture and financial literacy with entrepreneurial intentions.